2007
DOI: 10.4269/ajtmh.2007.76.676
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Serosurvey of Feline Leishmaniasis in Ecoregions Around the Northwestern Mediterranean

Abstract: A cross-sectional serosurvey using Leishmania infantum ELISA was performed on 445 cats living in ecoregions around the Northwestern Mediterranean basin; 58 cats from an area of the US where leishmaniasis is not endemic were used as negative controls. ELISA results were further confirmed in 69 cats by Western blot (WB). Finally, 76 of them were also tested for FeLV and FIV. Seroprevalence by ELISA-prot A was 6.29%, and that by ELISA-IgG was 5.25%. Positive cat sera recognized patterns of polypeptides in WB, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
108
4
24

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(148 citation statements)
references
References 30 publications
12
108
4
24
Order By: Relevance
“…On the other hand, Vides et al (2011) reported a higher seroprevalence by IFAT (10.9%) among cats sampled in the city of Araçatuba, state of São Paulo, which was higher than that found in this study, probably because all the cats sampled in the former study showed dermatologic lesions, one of the most suggestive clinical signs of feline leishmaniasis (SOLANO-GALLEGO et al, 2007). Sousa et al (2013) recently found high seroprevalence (100%) and high levels of L. infantum antibody titers ranged from 1:40 to 1:20480 among dogs sampled in the same area where this study was conducted.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…On the other hand, Vides et al (2011) reported a higher seroprevalence by IFAT (10.9%) among cats sampled in the city of Araçatuba, state of São Paulo, which was higher than that found in this study, probably because all the cats sampled in the former study showed dermatologic lesions, one of the most suggestive clinical signs of feline leishmaniasis (SOLANO-GALLEGO et al, 2007). Sousa et al (2013) recently found high seroprevalence (100%) and high levels of L. infantum antibody titers ranged from 1:40 to 1:20480 among dogs sampled in the same area where this study was conducted.…”
Section: Discussioncontrasting
confidence: 54%
“…Recently, Leishmania spp. infection in domestic cats has been reported in several countries, including Brazil, where this zoonosis is endemic (POLI et al, 2002;SOLANO-GALLEGO et al, 2007;SOUZA et al, 2005;SOBRINHO et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reservoirs for this parasite can include wild and domestic mammals, with domestic dogs serving as the most important reservoir in Brazil, where the disease is present in urban areas 1 . Infections in other pet animals, such as cats, have also been reported, mainly in certain European countries 2 as well as Brazil 3 . Although the role of cats in the epidemiology of VL has not been fully elucidated, data obtained from various studies suggest that this animal may act as secondary reservoirs or simply as accidental hosts.…”
Section: Visceral Leishmaniasis (Vl) Is a Protozoan Disease Caused Bymentioning
confidence: 99%
“…The occurrence of Leishmania in cats has been described by parasitological, molecular (HATAM et al, 2010;TABAR et al, 2008), and serological tests (DIAKOU et al, 2009;SOLANO-GALLEGO et al, 2007) as well as by IFA (MAROLI et al, 2007;AYLLON et al, 2008).…”
Section: Introductionmentioning
confidence: 99%